How digital influencer techniques can improve direct selling performance - Rizetto, Jordan Vile Tosoni (2021)
Direct selling has been transforming itself to adapt to social media, incorporating new ways of communication and relationship. This is an industry with 119 million independent representatives around the world and only a few studies are seeking to understand how these independent representatives have been using social media to leverage sales, to manage the relationship and retain clients, through techniques of Customer Relationship Management (CRM), as well as to comprehend what has been the impact of independent representatives who also happen to be social influencers upon the brands they work for. This dissertation, focused on the Brazilian market, shows that independent representatives with a great profile on social media and thousands of followers, acting as digital influencers, will not per se warrant better sales results. It is required that the industry focuses on developing new content on digital and social media, providing specialized social-selling training for its representatives, and create synergies with the lead conversion processes performed by these representatives through an ecosystem integrating the representative's social networks with the firm's networks and websites.